2001
DOI: 10.1034/j.1600-0447.2001.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in adolescents and young adults with suicidal behaviour

Abstract: A higher rate of anxiety in female suicide attempters results probably as a consequence of sexual abuse, which in turn makes them more vulnerable than males for attempting suicide between the age of 14-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 17 publications
9
53
2
8
Order By: Relevance
“…It was indicated in various studies that were conducted in our country that generally young and female populations attempt suicide. When we analyzed suicide cases in terms of genders, we found that higher rates of suicide were observed in females, which were consistent with the generally conducted studies (5,7,9,11,18,23,25,26). We considered that the reason for more females attempting suicide was that they are emotionally more fragile than men and have a higher tendency to attract attention and obtain secondary gains because of their social positions within the community.…”
Section: Discussionsupporting
confidence: 77%
“…It was indicated in various studies that were conducted in our country that generally young and female populations attempt suicide. When we analyzed suicide cases in terms of genders, we found that higher rates of suicide were observed in females, which were consistent with the generally conducted studies (5,7,9,11,18,23,25,26). We considered that the reason for more females attempting suicide was that they are emotionally more fragile than men and have a higher tendency to attract attention and obtain secondary gains because of their social positions within the community.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, elevated IL-13 in suicide women was observed but the differences were not significant. The finding of increased IL-13 in suicide men may be related to several other factors including those related to the reported gender effects in suicidal behavior (43,44) and the specific functions of this cytokine (45). In this regard, it should be highlighted that while there is abundant information about gender differences in suicide risk factors and suicidal behavior, to our knowledge, postmortem studies have not reported major neurochemical or gene expression differences between the brain of suicides women and men.…”
Section: Discussionmentioning
confidence: 80%
“…Sex differences in suicidal behavior have long been recognized (1)(2)(3)(4)(5). Studies have shown that men have higher suicide rates (1), while women are at higher risk for suicide attempts (2, 5).…”
Section: Introductionmentioning
confidence: 99%